The Impact of Hyperoxia on Outcome of Patients Treated with Noninvasive Respiratory Support - Pala Cifci, Seyhan (Can Respir J, 2020)
OBJECTIVE: Oxygen therapy is one of the most common treatment modalities for hypoxemic patients, but target goals for normoxemia are not clearly defined. Therefore, iatrogenic hyperoxia is a very common situation. The results from the recent clinical researches about hyperoxia indicate that hyperoxia can be related to worse outcomes than expected in some critically ill patients. According to our literature knowledge, there are not any reports researching the effect of hyperoxia on clinical course of patients who are not treated with invasive mechanical ventilation. In this study, we aimed to determine the effect of hyperoxia on mortality, and length of stay and also possible side effects of hyperoxia on the patients who are treated with oxygen by noninvasive devices. MATERIALS AND METHODS: One hundred and eighty-seven patients who met inclusion criteria, treated in Dokuz Eylul University Medical Intensive Care Unit between January 1, 2016, and October 31, 2018, were examined retrospectively. These patients' demographic data, oxygen saturation (SpO(2)) values for the first 24 hours, APACHE II (Acute Physiology and Chronic Health Evaluation II) scores, whether they needed intubation, if they did how many days they got ventilated, length of stay in intensive care unit and hospital, maximum PaO(2) values of the first day, oxygen treatment method of the first 24 hours, and the rates of mortality were recorded. RESULTS: Hyperoxemia was determined in 62 of 187 patients who were not treated with invasive mechanic ventilation in the first 24 hours of admission. Upon further investigation of the relation between comorbid situations and hyperoxia, hyperoxia frequency in patients with COPD was detected to be statistically low (16% vs. 35%, p < 0.008). Hospital mortality was significantly high (51.6% vs. 35.2%, p < 0.04) in patients with hyperoxia. When the types of oxygen support therapies were investigated, hyperoxia frequency was found higher in patients treated with supplemental oxygen (nasal cannula, oronasal mask, high flow oxygen therapy) than patients treated with NIMV (44.2% vs. 25.5%, p < 0.008). After exclusion of 56 patients who were intubated and treated with invasive mechanical ventilation after the first 24 hours, hyperoxemia was determined in 46 of 131 patients. Mortality in patients with hyperoxemia who were not treated with invasive mechanical ventilation during hospital stay was statistically higher when compared to normoxemic patients (41.3% vs 15.3%, p < 0.001). CONCLUSION: We report that hyperoxemia increases the hospital mortality in patients treated with noninvasive respiratory support. At the same time, we determined that hyperoxemia frequency was lower in COPD patients and the ones treated with NIMV. Conservative oxygen therapy strategy can be suggested to decrease the hyperoxia prevalence and mortality rates.